Ultrahigh Deep-Ultraviolet Responsivity of a β-Ga2O3/MgO Heterostructure-Based Phototransistor - Ahn, Jungho; Ma, Jiyeon; Lee, Doeon; Lin, Qiubao; Park, Youngseo; Lee, Oukjae; Sim, Sangwan; Lee, Kyusang; Yoo, Geonwook; Heo, Junseok (ACS Photonics, 2021)
Deep-ultraviolet (DUV) photodetectors based on wide-band-gap semiconductors have attracted significant interest across a wide range of applications in the industrial, biological, environmental, and military fields due to their solar-blind nature. As one of the most promising wide-band-gap materials, β-Ga2O3 provides great application potential over detection wavelengths ranging from 230 to 280 nm owing to its superior optoelectronic performance, stability, and compatibility with conventional fabrication techniques. Although various innovative approaches and device configurations have been applied to achieve highly performing β-Ga2O3 DUV photodetectors, the highest demonstrated responsivity of the β-Ga2O3 photodetectors has only been around 105 A/W. Here, we demonstrate a β-Ga2O3 phototransistor with an ultrahigh responsivity of 2.4 × 107 A/W and a specific detectivity of 1.7 × 1015 Jones, achieved by engineering a photogating effect. A β-Ga2O3/MgO heterostructure with an Al2O3 encapsulation layer is employed not only to reduce photogenerated electron/hole recombination but also to suppress the photoconducting effects at the back-channel surface of the β-Ga2O3 phototransistor via a defect-assisted charge transfer mechanism. The measured photoresponsivity is almost 2 orders of magnitude higher than the highest previously reported value in a β-Ga2O3-based photodetector, to the best of our knowledge. We believe that the demonstrated β-Ga2O3/MgO heterostructure configuration, combined with its facile fabrication method, will pave the way for the development of ultrasensitive DUV photodetectors utilizing oxide-based wide-band-gap materials.
Keywords: Charge transfer mechanisms; Detection wavelengths; Device configurations; Fabrication technique; Innovative approaches; Photogenerated electrons; Specific detectivity; Wide band-gap material; charge transfer; deep ultraviolet; photogating effect; phototransistor; ultrahigh responsivity; β-Ga2O3